Role of autophagy in ischemic stroke: insights from animal models and preliminary evidence in the human disease - Stanzione, Rosita; Pietrangelo, Donatella; Cotugno, Maria; Forte, Maurizio; Rubattu, Speranza (Frontiers in Cell and Developmental Biology, 2024)
Stroke represents a main cause of death and permanent disability worldwide. The molecular mechanisms underlying cerebral injury in response to the ischemic insults are not completely understood. In this article, we summarize recent evidence regarding the role of autophagy in the pathogenesis of ischemic stroke by reviewing data obtained in murine models of either transient or permanent middle cerebral artery occlusion, and in the stroke-prone spontaneously hypertensive rat.Few preliminary observational studies investigating the role of autophagy in subjects at high cerebrovascular risk and in cohorts of stroke patients were also reviewed. Autophagy plays a dual role in neuronal and vascular cells by exerting both protective and detrimental effects depending on its level, duration of stress and type of cells involved. Protective autophagy exerts adaptive mechanisms which reduce neuronal loss and promote survival. On the other hand, excessive activation of autophagy leads to neuronal cell death and increases brain injury. In conclusion, the evidence reviewed suggests that a proper manipulation of autophagy may represent an interesting strategy to either prevent or reduce brain ischemic injury.